PENGARUH CORPORATE GOVERNANCE TERHADAP MANAJEMEN PAJAK - Maria Meilinda; Nur Cahyonowati (Diponegoro Journal of Accounting, 2013)
This research investigates the influence of corporate governance influences on tax management behavior. Tax management is measured by effective tax rate. Corporate governance are measured by number of commissioner, percentage of independent commissioner, and compensation of commissioner and executives. Company size, profitability, debt ratio, and different tax rate are used as control variables.This research sample is manufactured company selected by using method of purposive sampling. There are 153 companies fulfilling criterions. This research used multiple regression analysis. The results of this research indicates that the number of commissioner, company size, profitability, and debt ratio affect tax management significantly. Meanwhile, the proportion of independent commissioners, compensation of commissioner and executive, and different tax rate does not significantly influence the company's tax management.